2011
DOI: 10.4172/2155-6156.1000152
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Gene Polymorphisms and Type 2 Diabetes among Singaporean Chinese Adults

Abstract: Background: Adiponectin is the most abundant circulating adipokine in human that regulates insulin actions. Association of adiponectin gene variations with type 2 diabetes (T2DM) has been reported albeit predominantly in non-Asian populations. Additionally, proof of variant functionality beyond statistical association is often unavailable. We studied six common (minor allele frequency ≥0.05) adiponectin single nucleotide polymorphisms (SNPs) in Singaporean Chinese adults with follow-up functional genetic exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Adiponectin is expressed in adipose tissue and low levels of it may cause reduction of fatty acid oxidation, elevated plasma glucose and insulin resistance, ultimately leading to T2DM [ 50 ]. The rs2241766-G of ADIPOQ gene significantly associated in this study was found to be associated with T2DM in another sample of south Indians [ 51 ] and in different other ethnic groups outside India—in Japanese [ 52 ], Singaporean Chinese [ 53 ], Han Chinese [ 54 ] and Iraqi populations [ 55 ]. Furthermore, the in-silico analysis also revealed that + 45 T>G polymorphism causes a synonymous change (G15G) and modulates the expression of adiponectin gene via affecting the splicing machinery [ 56 ].…”
Section: Discussionmentioning
confidence: 77%
“…Adiponectin is expressed in adipose tissue and low levels of it may cause reduction of fatty acid oxidation, elevated plasma glucose and insulin resistance, ultimately leading to T2DM [ 50 ]. The rs2241766-G of ADIPOQ gene significantly associated in this study was found to be associated with T2DM in another sample of south Indians [ 51 ] and in different other ethnic groups outside India—in Japanese [ 52 ], Singaporean Chinese [ 53 ], Han Chinese [ 54 ] and Iraqi populations [ 55 ]. Furthermore, the in-silico analysis also revealed that + 45 T>G polymorphism causes a synonymous change (G15G) and modulates the expression of adiponectin gene via affecting the splicing machinery [ 56 ].…”
Section: Discussionmentioning
confidence: 77%
“…This phenomenon might result from heterogeneity among racial groups; their impact on T2DM susceptibility are uncertain and worthy of follow‐up studies. The inconsistency of MAF was observed in different ethnic populations for both selected polymorphisms (Arikoglu et al., ; Hara et al., ; Hu et al., ; Li et al., ; Mohammadzadeh et al., ; Ramya et al., ; Toy, Liu, Cheng, Tan, & Lau, ). In this scenario, the present study was designed to establish the potential relationship of ADIPOQ −3971A/G (rs822396) and +276G/T (rs1501299) polymorphism with T2D subjects in a North Indian population (Punjab region).…”
Section: Discussionmentioning
confidence: 99%
“…Spanish individuals with both genotypes may jointly predispose to low adiponectin concentrations of the TNF-α and SNP 45 G allele of the adiponectin gene, potentially facilitating the production of impaired glucose tolerance or T2DM [ 72 ]. Adiponectin rs2241766 (SNP45T > G) polymorphism is closely linked to T2DM prevalence in South Indian population [ 6 ] and Singaporean Chinese adults [ 73 ]. The rs2241766 SNP (SNP45 T/G) of adiponectin gene is a risk factor for the development of T2DM in Iraqi population [ 74 ].…”
Section: Adiponectin Gene Polymorphisms In Different Types Of Diabetes Mellitusmentioning
confidence: 99%